A plasticizer-resistant semiconductor adhesive tape functional film material and a method for preparing the same

CN122958951APending Publication Date: 2026-10-23XIAMEN SHENGJI TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611302071.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]有鉴于此,本发明针对现有半导体用胶带中PVC增塑剂易析出导致残胶、粘附力下降的技术问题,提供一种耐增塑剂析出的半导体用胶带功能膜材料及其制备方法

Benefits of technology

(1)显著的增塑剂阻隔效果与双重阻隔机制:本发明在PVC基膜与压敏胶层之间引入松香酯底涂层,提出了“刚性分子屏障+极性致密网络”的双重阻隔机制,这是现有技术(如US4,284,681)所未揭示或教导的。该双重机制具体表现为:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a plasticizer-resistant-outgassing functional film material for semiconductor adhesive tape and a preparation method thereof, and belongs to the technical field of adhesive tape materials for semiconductor manufacturing. The functional film material comprises a PVC base film layer, a primer layer and a pressure-sensitive adhesive layer which are sequentially stacked. The primer layer is a coating layer formed after a rosin-modified polymer primer is coated and cured. The application introduces a rosin ester primer layer between the PVC base film and the pressure-sensitive adhesive layer, uses the rigid polycyclic structure and high-polarity intermolecular interaction to form a dense physical barrier layer, and effectively inhibits the migration and outgassing of small plasticizer molecules in the PVC. Experimental results show that the wafer surface cleanliness rating is A. The application also provides various modified embodiments and an online coating integrated preparation process, which can be widely applied to different semiconductor process requirements such as wafer cutting, grinding and packaging, and has a good industrial popularization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of tape materials for semiconductor manufacturing, and specifically to a functional film material for semiconductor tapes that is resistant to plasticizer precipitation and its preparation method. Background Technology

[0002] In semiconductor wafer manufacturing, thin film tapes such as dicing tapes and grinding tapes are widely used in wafer dicing, grinding, and packaging processes. To ensure the tapes have excellent resilience and flexibility, the substrate layer is typically made of polyvinyl chloride (PVC).

[0003] In the prior art, there are solutions that introduce a shielding layer between the pressure-sensitive adhesive and the flexible PVC substrate, such as US patents US4,284,681 and US4,045,600. However, these existing shielding layer solutions mostly employ polymer blending or coating methods, which have limited barrier effects and often suffer from problems such as insufficient adhesion to the upper and lower layers and difficulty in controlling coating uniformity, failing to effectively solve the performance degradation problem caused by long-term plasticizer migration. To address the above problems, the existing technologies mainly include the following two approaches: Firstly, reduce the amount of plasticizer added to PVC. Although this method can reduce the total amount of plasticizer leaching to some extent, the reduction in the amount of plasticizer added will directly lead to an increase in the hardness and a decrease in the flexibility of the PVC film. In precision processes such as wafer cutting, this can easily cause the film to crack or have poor adhesion, thus leading to process instability.

[0004] Secondly, plasticizer compositions with long carbon chain structures are used. Compared with traditional phthalate plasticizers, long carbon chain plasticizers have larger molecular volumes and lower migration rates, but they cannot fundamentally prevent the migration behavior of plasticizer molecules. With the extension of storage time, plasticizers will still slowly precipitate to the interface of the adhesive layer.

[0005] Therefore, there is an urgent need in this field for a functional tape film material and its preparation method that can effectively inhibit the long-term migration of small plasticizer molecules without changing the flexibility of the PVC base film. Summary of the Invention

[0006] In view of this, the present invention addresses the technical problem that PVC plasticizers in existing semiconductor tapes are prone to leaching, leading to residual adhesive and reduced adhesion, by providing a functional film material for semiconductor tapes that is resistant to plasticizer leaching and its preparation method.

[0007] Based on the above objectives, one or more embodiments of this specification provide a semiconductor tape functional film material resistant to plasticizer precipitation, comprising a PVC base film layer, a base layer, and a pressure-sensitive adhesive layer stacked sequentially; the base layer is a coating formed by coating and curing a rosin-modified polymer base agent.

[0008] Furthermore, the rosin-modified polymer is a rosin ester. Rosin esters have a rigid polycyclic structure (hydrophenanthrene ring structure), and the molecular chains form strong intermolecular interactions due to the presence of highly polar groups such as ester groups and carboxyl groups, which can self-assemble into a dense, high-cohesive base coating.

[0009] Further, the thickness of the rosin ester base coating is 0.5–2 μm. Preferably, the thickness of the rosin ester base coating is 0.5–1 μm.

[0010] Furthermore, the rosin ester primer is composed of rosin ester and an organic solvent, wherein the organic solvent is selected from one or more of toluene, ethyl acetate, and methyl ethyl ketone.

[0011] Furthermore, nanofillers may be added to the rosin ester base coating, wherein the nanofillers are selected from one or more of layered silicates, reduced graphene oxide, and nano silica.

[0012] Furthermore, the pressure-sensitive adhesive layer is an acrylic pressure-sensitive adhesive or a rubber pressure-sensitive adhesive.

[0013] This invention also provides a method for preparing the above-mentioned semiconductor tape functional film material resistant to plasticizer precipitation, comprising the following steps: (1) Dissolve rosin ester in an organic solvent to prepare a rosin ester primer solution; (2) The rosin ester primer solution is applied to at least one surface of a PVC base film and dried and cured to form a primer layer; (3) Apply pressure-sensitive adhesive to the base layer, and after drying and curing, form a pressure-sensitive adhesive layer to obtain the semiconductor tape functional film material resistant to plasticizer precipitation.

[0014] Furthermore, the coating method described in step (2) is gravure coating, micro-gravure coating, or slot coating.

[0015] Furthermore, the drying and curing temperature of the base coating in step (2) is 60 to 100°C.

[0016] Furthermore, the preparation method further includes: immediately after the PVC base film is calendered or cast into a film, the rosin ester primer is applied online, and then pressure-sensitive adhesive is applied to achieve one-time forming of the base film-barrier layer-adhesive layer.

[0017] The present invention has the following advantages over the prior art: (1) Significant plasticizer barrier effect and dual barrier mechanism: This invention introduces a rosin ester undercoat between the PVC base film and the pressure-sensitive adhesive layer, proposing a dual barrier mechanism of "rigid molecular barrier + polar dense network," which is not revealed or taught in existing technologies (such as US4,284,681). This dual mechanism is specifically manifested as follows: First layer: Geometric barrier (rigid molecular barrier): The rigid hydrogen phenanthrene ring polycyclic structure of rosin ester forms an impermeable rigid skeleton in the coating, which greatly increases the tortuosity (maze effect) of the diffusion path of small molecule plasticizers and significantly prolongs the time required for them to penetrate the coating.

[0018] The second layer: thermodynamic barrier (polar dense network): The densely packed ester and carboxyl groups on the rosin ester molecular chain form a dense network with high cohesive energy through strong hydrogen bonds and dipole-dipole interactions. This network has poor thermodynamic compatibility with plasticizer molecules with lower polarity, reducing the partition coefficient and diffusion coefficient of the plasticizer in the coating, thereby preventing its migration at the thermodynamic level.

[0019] Synergistic Effects and Unexpected Technical Benefits: The synergistic effect of the aforementioned dual mechanisms not only provides barrier efficiency far exceeding that of single physical barriers (as shown in the comparative examples), but also unexpectedly enhances the interfacial adhesion between the base coating and the PVC base film and pressure-sensitive adhesive layer (the polar groups of rosin ester can form good bonds with both PVC and acrylate adhesive layers), without sacrificing the flexibility of the PVC base film. This integrated "barrier-adhesion" performance is something that existing technologies could not have anticipated.

[0020] (2) No sacrifice of base film flexibility: The present invention does not require reducing the amount of plasticizer added in PVC, so it will not cause an increase in the hardness of PVC film and can maintain the good flexibility and adhesion performance of tape.

[0021] (3) Excellent interfacial adhesion: The rosin ester base coating has excellent adhesion to the PVC base film and pressure-sensitive adhesive layer, avoiding the problem of easy peeling and falling off of the coating in the prior art, and ensuring the long-term stability of the overall structure. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of this disclosure clearer, the following detailed description is provided in conjunction with specific embodiments. The performance advantages described in each embodiment can be attributed to the unique dual-barrier mechanism of "rigid molecular barrier + polar dense network" of this invention. Example 1

[0023] (a) Raw materials and preparation: In this embodiment, glycerol rosin ester (industrial grade, acid value ≤10mg KOH / g, purchased from Guangxi Wuzhou Rosin Co., Ltd.) with a softening point of 85℃ was selected as the rosin-modifying polymer. Industrial grade toluene (purity ≥99.5%, water content ≤0.05%) was used as the solvent. At room temperature (25±2℃), toluene was first added to a stainless steel mixing tank equipped with a stirrer. The stirrer was started at 200 rpm, and glycerol rosin ester particles were slowly added while stirring. After the addition was complete, the stirring speed was increased to 300 rpm, and stirring was continued for 30 minutes until the rosin ester particles were completely dissolved, and the solution was a uniform, transparent, pale yellow liquid. Using a Forecast-4 cup viscometer, the viscosity of this solution was approximately 35 seconds (25℃). Toluene was then added to adjust the solid content, ultimately preparing a rosin ester primer solution with a solid content of 10wt%. After preparation, the solution was allowed to stand for 15 minutes to defoam before use.

[0024] (II) Primer coating process: A PVC base film with a thickness of 80μm (plasticizer DOP added at 45phr, light transmittance ≥90%) was selected. Before unwinding, the PVC base film was placed in a constant temperature and humidity room (23±2℃, relative humidity 55±5%) for 24 hours to balance in order to reduce the dimensional fluctuations of the base film caused by moisture absorption or temperature changes.

[0025] A gravure coating machine (150 lines / inch gravure roller, 200mm diameter) was used for coating. The rosin ester primer solution was pumped into the doctor blade chamber of the gravure roller, and the roller speed was synchronized with the coating speed. The coating speed was set to 10m / min, the contact pressure between the gravure roller and the base film was 0.3MPa, and the doctor blade pressure was 0.15MPa. The appearance of the wet film was monitored in real time during the coating process to ensure no missed coating, lines, or streaks.

[0026] After coating, the PVC base film, still wet, is placed in a five-section, independently temperature-controlled suspended oven for drying and curing. The temperatures of each section are set as follows: Section 1 70℃, Section 2 75℃, Section 3 80℃, Section 4 80℃, and Section 5 75℃, with a total drying time of 1.5 minutes. After removal from the oven, the film is allowed to cool naturally to room temperature. An online infrared thickness gauge (accuracy ±0.02μm) is used to monitor the base coating thickness in real time. By adjusting the contact pressure between the gravure roller and the base film, the dry film thickness of the base coating is controlled to 0.5μm (target value). The measured thickness range is 0.48~0.52μm, meeting the accuracy requirements.

[0027] (III) Coating of pressure-sensitive adhesive layer: Pressure-sensitive adhesive (PSAs) was applied to the base coat surface after it had cooled to room temperature. A solvent-based acrylic PSA (40% solids content, 4500 cP / 25℃ viscosity, approximately 65% ​​gel fraction) was used. A doctor blade applicator was employed, with a 50 μm gap and a coating speed of 8 m / min. After coating, the PSA was dried and cured in a three-section oven at 90℃, 100℃, and 95℃ for a total drying time of 3 minutes, forming a 20 μm thick PSA layer. A release film (38 μm thick, 0.8 g / m² silicone oil coating) was then laminated, cooled to room temperature by cooling rollers, and finally wound up.

[0028] (iv) Purpose and Application Scenarios: The adhesive tape functional film material prepared in this embodiment has a thin (0.5μm) and highly transparent base coating with excellent light transmittance (≥88%), which does not affect the identification and positioning of the cutting path under a microscope during wafer dicing. It is particularly suitable for silicon wafer dicing processes of 8 inches and below. Due to the extremely thin coating, it hardly affects the original resilience of the PVC base film (the elongation at break of the base film remains ≥280%). During the high-speed rotating blade cutting process, it can closely adhere to the curved surface of the wafer, effectively preventing adjacent grain contamination caused by cutting debris. At the same time, through the barrier effect of the base coating on plasticizers, it ensures that no plasticizer seeps into the pressure-sensitive adhesive layer during the vacuum nozzle pickup and transfer of the grains after cutting, thus preventing a decrease in adhesion. This achieves 100% non-destructive pickup with no adhesive residue. The reason why this extremely thin coating can achieve high-efficiency barrier is due to the fact that the rosin ester base coating can still form a highly ordered rigid molecular skeleton and polar dense network at an extremely thin thickness, which is impossible for traditional polymer coatings.

[0029] Summary table of process parameters

[0030] Example 2 (a) Raw materials and preparation: In this embodiment, glycerol rosin ester with a softening point of 85℃ was also selected as the rosin-modifying polymer. To investigate the effect of different solvent systems on the coating effect, a mixed solvent of ethyl acetate (purity ≥99.7%) and butanone (purity ≥99.5%) was selected at a volume ratio of 1:1. The mixed solvent was added to the mixing tank at room temperature, and glycerol rosin ester was added while stirring at a stirring speed of 350 r / min for 40 minutes until completely dissolved. The viscosity was measured using a Forte 4 cup viscometer, and the viscosity was approximately 38 seconds. Subsequently, the mixed solvent was added to prepare a rosin ester primer solution with a solid content of 12 wt%, which was allowed to stand for 20 minutes to defoam before use.

[0031] (II) Primer coating process: Microgravure coating was used (gravure roller mesh count 200 lines / inch, roller diameter 150mm). Compared to conventional gravure coating, microgravure coating, with its reverse coating method, is better suited for high-speed thin-layer coating, resulting in superior coating uniformity. The coating speed was set to 8 m / min (slightly lower than in Example 1 to increase coating amount and achieve the target thickness), the ratio of gravure roller speed to machine speed was 1.2:1 (reverse operation), and the doctor blade pressure was 0.12 MPa. The oven temperature was set to five stages: 75℃, 80℃, 85℃, 85℃, and 80℃, with a total drying time of 2 minutes. The thickness was controlled using a β-ray online thickness gauge, and the final dry film thickness was controlled to 1.0 μm (measured range 0.97–1.03 μm) by adjusting the gravure roller speed ratio.

[0032] (III) Coating of pressure-sensitive adhesive layer: Similar to Example 1, the same acrylic pressure-sensitive adhesive of the same specifications was used, and the coating and drying curing were carried out under the same conditions to form a pressure-sensitive adhesive layer with a thickness of 20 μm. After laminating the release film, the layer was wound up.

[0033] (iv) Purpose and Application Scenarios: In this embodiment, the base coating thickness is moderate (1 μm). The 1 μm dense rosin ester coating fully utilizes its dual barrier mechanism: the rigid multi-ring structure forms a skeletal barrier, while the polar network further reduces the solubility of the plasticizer in the coating. Together, they ensure that plasticizer migration is effectively suppressed under heated conditions, exhibiting both excellent plasticizer barrier performance and interfacial adhesion (peel strength between the base coating and the PVC substrate ≥ 3.5 N / 25 mm). This is particularly suitable for the back-side polishing process of 12-inch large-size silicon wafers. Large-size wafers are subjected to significant mechanical stress and polishing heat during polishing (the polishing zone temperature can reach 40–60°C), accelerating the migration rate of plasticizers under heated conditions. The 1 μm dense rosin ester coating provides superior plasticizer shielding without increasing the rigidity of the substrate, effectively preventing the polishing fluid (usually containing surfactants and water) and plasticizer from penetrating to the adhesive layer interface, leading to bubbling, slippage, or abnormal adhesion. Meanwhile, stable adhesion ensures that the wafer thickness uniformity (TTV) after polishing is controlled within ±1.5μm, meeting the requirements of high-end chip manufacturing.

[0034] Summary table of process parameters

[0035] Example 3 (a) Raw materials and preparation: To verify the applicability of different types of rosin esters, this embodiment selected pentaerythritol rosin ester (softening point 100℃, acid value ≤8mg KOH / g, industrial grade), which has a higher softening point, as the rosin-modifying polymer. Pentaerythritol rosin ester contains four ester functional groups in its molecular structure, exhibiting higher functionality and a larger molecular weight compared to glycerol rosin ester, theoretically enabling the formation of a coating network with higher crosslinking density. Toluene was used as the solvent. Given the high viscosity and slow dissolution rate of pentaerythritol rosin ester, this embodiment employed a heating-assisted dissolution process: toluene was first added to the mixing tank, heated to 45℃ in a water bath, and pentaerythritol rosin ester particles were added while stirring. The stirring speed was increased to 400 r / min, and stirring was continued for 50 minutes until completely dissolved. Heating was then turned off, and the mixture was allowed to cool naturally to room temperature. A primer solution with a solid content of 15wt% was prepared (due to the high viscosity of this rosin ester, the solid content was appropriately increased to ensure coating flowability), with a Ford cup viscosity of approximately 42 seconds. Let stand for 30 minutes to defoam, then set aside.

[0036] (II) Primer coating process: Slit coating was employed (slit die gap 0.08mm, die width 300mm, die-to-base film distance 0.15mm). Slit coating offers precise control over coating amount and excellent uniformity of wet film thickness, making it suitable for precision coating of medium-thickness coatings. The coating machine speed was set to 12m / min, and the feed pump flow rate was set to 80mL / min. The oven temperature was set to a four-stage stepped heating process: 90℃ in the first stage, 100℃ in the second stage, 100℃ in the third stage, and 95℃ in the fourth stage, with a total drying time of 1.8 minutes. The thickness was measured using a white light interferometer, controlling the dry film thickness to 1.5μm (actual measured thickness 1.45~1.55μm).

[0037] (III) Coating of pressure-sensitive adhesive layer: Same as Example 1.

[0038] (iv) Purpose and Application Scenarios: Due to its higher softening point (100°C) and greater density of rigid phenanthrene rings, pentaerythritol rosin ester exhibits a significantly stronger geometric barrier effect than ordinary glycerol rosin ester. Furthermore, its higher crosslinking density restricts molecular chain movement at high temperatures, resulting in superior coating structural stability. This embodiment is particularly suitable for semiconductor packaging tapes involving high-temperature soldering or reflow soldering processes, such as packaging carrier tapes or thermoforming tapes used in QFN (Quad Flat No-Leader) and BGA (Ball Grid Array) packages. In these applications, the tape may briefly withstand peak temperatures of 150°C to 180°C during the packaging process. At these temperatures, traditional primers soften or even melt, losing their barrier function and causing severe plasticizer precipitation that contaminates gold wires or pads. The high softening point rosin ester coating of this embodiment maintains solidity and structural integrity at high temperatures, effectively preventing large-scale migration of plasticizers under welding thermal shock, and ensuring the bonding strength and reliability of the encapsulated solder joints. However, the high softening point pentaerythritol rosin ester, with its higher crosslinking density and denser rigid hydrogen phenanthrene ring structure, elevates the geometric barrier effect (first layer) and network stability to a new level. Even under thermal shock at 150-180℃, its polar network remains dense and stable, while the molecular chain movement of traditional polymer coatings intensifies at this temperature, and the barrier performance will quickly fail.

[0039] Summary table of process parameters

[0040] Example 4 (a) Raw materials and preparation: This embodiment introduces nanosheet fillers into a rosin ester matrix to construct an organic-inorganic composite barrier coating. Glyceryl rosin ester (softening point 85℃) was selected as the matrix resin. Toluene was used as the solvent. The nanofiller was layered silicate nanoclay (montmorillonite type, trade name Cloisite® Na⁺, average sheet diameter approximately 500nm, aspect ratio approximately 50, cation exchange capacity 92meq / 100g).

[0041] The preparation process is as follows: First, weigh the nano-clay powder according to the formula and add it to toluene solvent. Pre-disperse the powder using an ultrasonic cell disruptor (power 500W, frequency 40kHz, working mode: 3 seconds of sonication / 2 seconds of pause, total effective sonication time 30 minutes). Then, transfer the pre-dispersed nano-clay suspension to a mixing tank, add glycerol rosin ester, and stir at 350 rpm for 45 minutes to allow rosin ester molecules to fully intercalate between the nano-clay layers. Finally, prepare a homogeneous composite primer solution with a rosin ester solid content of 10 wt% and a nano-clay addition amount of 5% of the rosin ester solid mass. Let it stand for 30 minutes to defoam before use.

[0042] (II) Primer coating process: Given the thixotropic and thickening effects of the nanocomposite dispersion, its coating adaptability is slightly reduced. This embodiment employs gravure coating (gravure roller mesh count 180 lines / inch, slightly higher than in Example 1 to achieve a lower coating weight), with the coating speed set at 6 m / min (appropriately reduced to ensure sufficient leveling time for the nanocomposite dispersion), and the gravure roller pressure at 0.35 MPa. The oven temperature was set to a constant 80°C, and the total drying time was 2.2 minutes. An infrared thickness gauge was used to monitor and control the final composite undercoat dry film thickness to 0.5 μm (measured at 0.48–0.53 μm).

[0043] (III) Coating of pressure-sensitive adhesive layer: Same as Example 1.

[0044] (iv) Purpose and Application Scenarios: During the coating drying process, layered silicate nanosheets tend to align parallel to the base film surface, forming a tortuous diffusion path resembling a "brick wall" structure (i.e., the "maze effect"), which significantly extends the diffusion distance required for plasticizer molecules to penetrate the coating. Compared to pure rosin ester coatings, the permeability of plasticizers in the nanocomposite coating can be reduced by 50% to 70%. This embodiment is particularly suitable for long-term storage of spare wafer processing tapes, i.e., tape products that need to be stored for more than 6 months after manufacturing before being used by the end customer. Even in extreme storage environments (such as the high temperature of 60°C and 90% relative humidity that may be reached during summer container transportation), the composite coating can still maintain an extremely low plasticizer permeability, ensuring that the peel performance of the tape is basically the same as that of freshly prepared tape when it is released from the warehouse, solving the problem of difficult tape inventory management in the semiconductor supply chain; the "maze effect" of layered silicates significantly enhances the first layer of geometric barrier, and works in conjunction with the rigid framework of rosin ester itself to form a multi-scale ultra-long diffusion path, which multiplies the time required for plasticizers to penetrate the coating, perfectly meeting the challenges of long-term storage.

[0045] Summary table of process parameters

[0046] Example 5 (a) Raw materials and preparation: In this embodiment, reduced graphene oxide (rGO) nanosheets were selected as the functional nanofiller. (Note: Reduced graphene oxide (rGO) has good electronic conductivity due to the removal of most oxygen-containing functional groups, restoring the sp2 carbon network, and can be used for antistatic purposes; while graphene oxide (GO) itself is an electrical insulator and does not possess this function.) The rGO sheets have a diameter of 1–5 μm and a thickness of approximately 1 nm. Butanone was used as the solvent, and glycerol rosin ester was used as the matrix resin.

[0047] The preparation process is as follows: Reduced graphene oxide powder is added to methyl ethyl ketone (MEK) solvent and ultrasonically dispersed using a low-temperature probe (dispersion temperature controlled ≤10℃ to prevent excessive solvent evaporation and thermal reduction of reduced graphene oxide). The ultrasonic parameters are: power 300W, working mode 3 seconds of ultrasonication / 2 seconds of pause, total effective ultrasonic time 20 minutes. The reduced graphene oxide dispersion is then transferred to a mixing tank, glycerol rosin ester is added, and the mixture is stirred at 300 rpm for 30 minutes to prepare a composite primer solution with a rosin ester solid content of 8 wt% and a reduced graphene oxide addition amount of 2% of the rosin ester mass. The viscosity was measured using a Ford cup 4 viscometer, and was approximately 45 seconds (the sheet-like structure of the reduced graphene oxide increases the system viscosity). The mixture was allowed to stand for 30 minutes to defoam before use.

[0048] (II) Primer coating process: The reduced graphene oxide dispersion exhibits strong thixotropy (it is gel-like when stationary and thins upon shearing), necessitating a microgravure coating method to obtain a uniform wet film coating. The coating speed was set to 5 m / min, the gravure roller mesh count to 200 lines / inch, and the speed ratio to rotation speed to speed of 1.5:1 (reverse). The oven temperature was set to 90℃, and the total drying time was 2.5 minutes. The final dry film thickness of the composite undercoat was controlled to be 0.8 μm (measured at 0.76–0.85 μm).

[0049] (III) Coating of pressure-sensitive adhesive layer: Same as Example 1.

[0050] (iv) Purpose and Application Scenarios: Reduced graphene oxide not only possesses the physical barrier effect brought about by its two-dimensional sheet structure, but more importantly, its abundant oxygen-containing functional groups (hydroxyl, epoxy, and carboxyl groups) endow the coating with certain electronic conductivity and excellent antistatic properties (surface resistivity can be reduced to 10). 8 ~10 9 The Ω·sq of pure rosin ester coating is approximately 10¹³ Ω·sq. This embodiment is particularly suitable for wafer dicing processes of high-frequency / RF devices that are extremely sensitive to electrostatic discharge (ESD), with typical applications including 5G communication chips, millimeter-wave radar chips, and power amplifier chips. When using the tape of this embodiment for dicing, the tape can effectively dissipate the static charge generated by friction during dicing by reducing the conductive network of graphene oxide while preventing the plasticizer from precipitating. This prevents the accumulation of static electricity from causing the delicate gate structure on the wafer to be broken down or the gate oxide layer to be damaged, significantly improving the dicing yield of high-value chips (the improvement can reach 5% to 10%).

[0051] This embodiment, in addition to achieving the dual mechanism of plasticizer barrier, also provides antistatic function, making it particularly suitable for device manufacturing processes that are sensitive to static electricity.

[0052] Summary table of process parameters

[0053] Example 6 (a) Raw materials and preparation: A low-viscosity primer solution with a solid content of 8 wt% was prepared by dissolving glyceryl rosin ester (softening point 85℃) in ethyl acetate. The low-solids content formulation primarily considers the need for rapid drying within the limited oven length during online coating; the low solids content facilitates rapid solvent evaporation. Using a Ford cup 4 viscometer, the viscosity was measured to be approximately 28 seconds, suitable for high-speed cast coating.

[0054] (II) Online integrated preparation process: This embodiment adopts a continuous production line solution that integrates PVC casting and base coating, eliminating the traditional step-by-step process of "first making PVC base film rolls → offline unwinding and coating → then rewinding", and achieving seamless connection between base film forming and barrier layer coating.

[0055] The specific process is as follows: After PVC resin is extruded and plasticized, molten sheets are extruded through a T-shaped casting die. These sheets are then shaped by a three-roll calender and initially cooled by a cooling roller to a film surface temperature of approximately 60-70°C. At this point, the PVC film surface is still in a slightly molten or highly elastic state with high surface activity. In this state, the primer solution is immediately applied online to one surface of the PVC film through a slit coating die located behind the cooling roller. The slit die gap is set to 0.06 mm, and the coating speed is synchronized with the casting line speed, set to 25 m / min (medium-high speed production). The wet film coating amount is precisely controlled by the feed pump speed. After coating, the PVC film, carrying the wet film, immediately enters a 15-meter-long suspended hot air oven. The oven temperature is set to 100°C, and the total drying time is approximately 36 seconds, allowing the solvent to completely evaporate and the rosin ester to cure on the PVC surface, forming a primer coating. Next, a rubber-based heat-resistant pressure-sensitive adhesive (45% solids content, 6000 cP / 25℃ viscosity) is applied online to the base coating surface using a comma-shaped doctor blade coating head, with the coating gap controlled at 55 μm. It is then dried and cured in a 120℃ hot air drying oven to form the pressure-sensitive adhesive layer. Thus, a single production line achieves a one-time process of "PVC base film forming → rosin ester barrier layer coating → pressure-sensitive adhesive layer coating". After laminating the release film, it is cooled and wound up.

[0056] (III) Explanation of technological advantages: The online coating process in this embodiment has significant advantages over offline coating: First, it eliminates the unwinding, rewinding, and intermediate storage steps in offline coating, saving equipment investment and factory space, and reducing energy consumption per unit product by about 15% to 20%; Second, coating is performed on the PVC film surface before it is completely cooled, and the solvent in the rosin ester primer has a moderate swelling effect on the PVC surface, promoting physical entanglement and micro-melting and mutual dissolution between the rosin ester molecular chains and the PVC surface molecular chains, significantly enhancing the interfacial bonding force between the primer layer and the PVC base film (peel strength ≥4.5N / 25mm, about 25% higher than offline coating).

[0057] (iv) Purpose and Application Scenarios: This embodiment's online integrated process combines high performance and low cost, making it particularly suitable for the large-scale, high-volume industrial manufacturing of consumer-grade semiconductor packaging tapes, such as LED packaging surface mount tapes and discrete device packaging tapes. These products have high market demand and are price-sensitive, yet still require high long-term reliability. This embodiment achieves sufficiently high plasticizer barrier properties at a relatively low cost, preventing the LED packaging tape from shifting or detaching due to adhesion degradation under long-term lighting and heat conditions, thus improving the long-term lifespan and reliability of LED luminaires.

[0058] The advantage of online integration lies in utilizing the active state of the PVC film surface before it is fully cooled, which allows the rosin ester molecular chains to physically entangle and micro-melt and dissolve with the PVC surface. This further strengthens the interfacial bonding between the base coating and the base film, providing a structural basis for the stable performance of the dual barrier mechanism.

[0059] Summary table of process parameters

[0060] Example 7 (a) Raw materials and preparation: This embodiment uses the same glycerol rosin ester and toluene solvent as Example 1, but to improve the drying efficiency of the thick coating, the solid content is increased to 18 wt% to reduce solvent load and drying time. The preparation process is the same as in Example 1, and the viscosity at the Forecast 4 cup is approximately 48 seconds.

[0061] (II) Primer coating process: A slot coating method (0.15mm slot gap) was used, with the coating speed reduced to 5m / min to obtain a thicker wet film coating. Oven drying employed a stepped low-temperature-high-temperature combination process: the first stage was 70℃ for 2 minutes (low-temperature, slow drying to prevent skinning of the thick coating surface and subsequent solvent residue); the second stage was 80℃ for 1.5 minutes; the third stage was 100℃ for 1.5 minutes (high-temperature acceleration for deeper drying); and the fourth and fifth stages were 85℃ for 1 minute (post-curing), with a total drying time of approximately 6 minutes. Offline sampling with a micrometer was used to control the final dry film thickness to 2.0μm (actual measured thickness 1.9–2.1μm).

[0062] (III) Coating of pressure-sensitive adhesive layer: Same as Example 1.

[0063] (iv) Purpose and Application Scenarios: The 2μm thick coating provides the highest level of "absolute barrier safety" in this invention. Even in extreme formulations with extremely high plasticizer content in the PVC base film (e.g., DOP ≥ 50 phr), it ensures no detectable penetration of the plasticizer during long-term use (ATR-FTIR detection of plasticizer characteristic peaks on the adhesive surface showed no detection after 6 months). This embodiment is particularly suitable for the integrated thinning and dicing process of ultra-thin wafers (thickness < 50μm). The in-plane uniformity of tape adhesion is extremely critical during the thinning and dicing of ultra-thin wafers. Any slight local penetration of plasticizer leading to uneven adhesion will cause stress concentration during thinning and grinding or blade cutting, resulting in wafer breakage (i.e., "edge chipping" or "fracture"). The 2μm thick coating provides maximum safety redundancy, ensuring consistent tape adhesion throughout the continuous thinning-dicing process, which can last for several hours, reducing the breakage rate of ultra-thin wafer processing from 3%–5% in traditional methods to below 0.1%.

[0064] The 2μm thick base coating provides maximum "absolute barrier safety," representing the "strength" limit test of the invention's dual barrier mechanism. Results show that even with PVC containing extremely high plasticizer content, the mechanism still provides undetectable barrier performance, demonstrating its superior barrier efficiency and reliability.

[0065] Summary table of process parameters

[0066] Example 8 (a) Raw materials and preparation: Same as in Example 1, glycerol rosin ester / toluene solution, solid content 12 wt%.

[0067] (II) Primer coating process: This embodiment aims to verify the process feasibility of the present invention under high-temperature and high-speed coating conditions. Gravure coating was used (same as in Example 1), with the coating speed significantly increased to 20 m / min (simulating the operating conditions of an industrial high-speed coating production line). To match the rapid drying capacity required for high-speed coating, the oven temperature was uniformly increased to 100℃ (all five sections were at 100℃), shortening the total drying time to 1.0 minute. Although the drying time was significantly shortened, the high temperature accelerated the solvent evaporation rate and the spreading and leveling of the rosin ester, still resulting in a uniform-looking and well-adhesive base coating (dry film thickness 1.2 μm, measured 1.15–1.25 μm).

[0068] (III) Coating of pressure-sensitive adhesive layer: Same as Example 1.

[0069] (iv) Purpose and Application Scenarios: This embodiment verifies the process adaptability of the technical solution of the present invention on a high-speed industrial coating production line. Its core significance is that existing tape manufacturers do not need to change any major production equipment. They only need to replace the ordinary primer (such as traditional acrylic primer) with the rosin ester primer of the present invention, and at the same time appropriately increase the oven temperature (from the conventional 80°C to 100°C). This allows them to directly produce high-end semiconductor tape products resistant to plasticizer precipitation on existing high-speed coating production lines (with speeds up to 100 m / min).

[0070] The technical solution of this embodiment has significant practical implications for the product upgrading and transformation of traditional tape manufacturers, enabling them to quickly enter the high-end semiconductor tape market with relatively low investment in technological transformation, and significantly improve product added value and market competitiveness. Typical application companies include existing PVC tape, electrical tape, and packaging tape manufacturers that are transforming into the semiconductor cutting tape field.

[0071] (V) Summary table of process parameters for Example 8

[0072] Comparative Example 1 (a) Preparation process: The difference from Example 1 is that no primer coating process is performed; that is, no surface primer treatment is applied to the PVC base film. The same acrylic pressure-sensitive adhesive as in Example 1 is directly coated onto the corona-treated (surface tension ≥42 dyne / cm) PVC base film surface, dried and cured, and then a release film is applied. The remaining steps are exactly the same as in Example 1.

[0073] Results Comparison: In this comparative example, due to the lack of a base coating for double protection, the plasticizer quickly migrates to the adhesive surface, resulting in extremely poor resistance to plasticizer exudation and a rapid decrease in adhesion.

[0074] Comparative Example 2 (a) Raw materials and preparation: A commercially available conventional acrylic primer (mainly thermoplastic acrylic resin, Tg approximately 50°C, linear molecular weight, and rigid polycyclic structure without rosin) was selected and diluted with toluene to a solid content of 10 wt%. The preparation process was the same as in Example 1.

[0075] (II) Primer coating process: The acrylate primer was applied to a PVC base film of the same specifications under the same microgravure coating process conditions as in Example 2 (coating speed 8m / min, oven temperature 80℃, total drying time 2 minutes), and the dry film thickness was controlled to be 1.0μm.

[0076] (III) Coating of pressure-sensitive adhesive layer: Same as Example 1.

[0077] Results Comparison: Using traditional linear acrylic resin as the base coating, its molecular chains lack a rigid framework, and the polar network is not dense enough to form an effective double barrier. Therefore, its barrier effect against plasticizers is far inferior to that of the rosin ester base coating of this invention, and its adhesion to the PVC base film is also weaker.

[0078] Comparative Example 3 (a) Raw materials and preparation: Hydrogenated rosin ester (softening point 80℃, acid value ≤10mg KOH / g) was selected as the raw material for the primer and a solution with a solid content of 12wt% was prepared with toluene. The preparation process was the same as in Example 1.

[0079] (II) Primer coating process: The same microgravure coating process conditions as in Example 2 were used to control the dry film thickness to 1.0 μm.

[0080] (III) Coating of pressure-sensitive adhesive layer: Same as Example 1.

[0081] Results Comparison: Using hydrogenated rosin esters, some double bonds are saturated. Although it still possesses a certain degree of rigidity, the content of polar groups is reduced, resulting in insufficient strength of the polar dense network formed. This indicates that the synergy between the "polar dense network" (secondary barrier) and the "rigid molecular barrier" (firstary barrier) is crucial to this invention; neither can be dispensed with.

[0082] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of this disclosure (including the claims) is limited to these examples; within the framework of this disclosure, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of different aspects of one or more embodiments of this specification as described above, which are not provided in detail for the sake of brevity.

[0083] Although this disclosure has been described in conjunction with specific embodiments thereof, many substitutions, modifications and variations of these embodiments will be apparent to those skilled in the art from the foregoing description.

[0084] One or more embodiments of this specification are intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of one or more embodiments of this specification should be included within the scope of protection of this disclosure.

Claims

1. A semiconductor tape functional film material resistant to plasticizer precipitation, characterized in that, It includes a PVC base film layer, a base layer and a pressure-sensitive adhesive layer stacked in sequence; the base layer is a coating formed by applying and curing a rosin-modified polymer base agent.

2. The semiconductor tape functional film material resistant to plasticizer precipitation according to claim 1, characterized in that, The rosin-modified polymer is a rosin ester, which is selected from one or more of glycerol rosin ester and pentaerythritol rosin ester.

3. The semiconductor tape functional film material resistant to plasticizer precipitation according to claim 1, characterized in that, The thickness of the base coating is 0.5 to 2 μm.

4. The semiconductor tape functional film material resistant to plasticizer precipitation according to claim 1, characterized in that, The rosin ester base coating also contains nanofillers, which are selected from one or more of layered silicates, reduced graphene oxide, and nano silica.

5. The semiconductor tape functional film material resistant to plasticizer precipitation according to claim 1, characterized in that, The pressure-sensitive adhesive layer is an acrylic pressure-sensitive adhesive or a rubber pressure-sensitive adhesive.

6. A method for preparing a semiconductor tape functional film material resistant to plasticizer precipitation as described in any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Dissolve the rosin-modified polymer in an organic solvent to prepare a primer solution; (2) The primer solution is applied to at least one surface of the PVC base film and dried and cured to form a primer layer; (3) Apply pressure-sensitive adhesive to the base layer, and after drying and curing, form a pressure-sensitive adhesive layer to obtain the semiconductor tape functional film material resistant to plasticizer precipitation.

7. The preparation method according to claim 6, characterized in that, The coating method described in step (2) is gravure coating, micro-gravure coating or slot coating.

8. The preparation method according to claim 6, characterized in that, The drying and curing temperature in step (2) is 60 to 100°C.

9. The preparation method according to claim 6, characterized in that, The rosin-modified polymer is a rosin ester, which is selected from one or more of glycerol rosin ester and pentaerythritol rosin ester.

10. The preparation method according to claim 6, characterized in that, The preparation method further includes: immediately after the PVC base film is calendered or cast into a film, the primer solution is coated online, and then pressure-sensitive adhesive is coated to achieve one-time forming of base film-barrier layer-adhesive layer.

Citation Information

Patent Citations

  • Method of inhibiting plasticizer migration from plasticized poly(vinyl chloride) substrates

    US4045600A

  • Composite sheet material

    US4284681A